Engagement de femmes en milieu évangélique norvégien : un lieu de tensions entre héritages féministes et religieux - Frédérique Harry (Amnis)
Based on a study of the evangelical women’s association « Women in network », this paper aims at showing the specificities of Christian women’s involvement in Norway. The main purpose of this article is to focus on the peculiarities of Christian women’s activism in a country where feminist ideologies have strongly affected the society, politics and culture. This study is based on a historical approach of the evolution of women’s role and involvement in the Christian public sphere in Norway. This article tries to point up continuity and change of forms of involvement in order to enhance discussions on the interactions between religious involvement and women’s affirmation in the public sphere.